(untitled) (Marketing Journal, 2025)
This article addresses the development of scientifically and practically significant proposals and recommendations aimed at the comprehensive development of the agricultural products market in the agrarian sector within the framework of free market princip les. The study focuses on improving market competitiveness, ensuring food security, and maintaining sustainable development of the agrarian market under current economic and environmental conditions.